Study on Implementation of China's Central Bank Digital Currency to Improve Financial Inclusion in Indonesia - Ariardi, Falah Ahmad; Pati, Umi Khaerah (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Central Bank Digital Currency (CBDC) has emerged as focal point for global monetary policy authorities as an effort to enhance financial inclusion. This study aims to investigate the regulation and implementation of CBDC in Indonesia by referring to China's experience in implementing e-CNY or China’s CBDC. The method used is a normative legal research method with a statutory and comparative approach through the exploration of regulations and governance that can be adopted by Indonesia in implementing CBDC as an instrument to improve financial inclusion. The analysis reveals that China's experience in implementing e-CNY provides valuable insights for Indonesia in designing and implementing CBDC. Prerequisites in implementing CBDC includes a strong blockchain technology infrastructure, strict data protection, and partnerships between the central bank and financial service providers. This study further illustrates the potential for CBDC’s implementation and implications for the financial sector.